The Human World as Augmented Reality: Transcendentalism and Anthropological Difference = Žmogaus pasaulis kaip tikrovės prieaugis : transcendentalizmas ir antropologinis skirtumas - Chiurazzi, Gaetano (Religija ir kultūra, 2017)
[full article, abstract in English; abstract in Lithuanian]In this paper, I discuss, first of all, the positions of Perter Singer and Jacques Derrida regarding the difference between humans and animals. Singer’s animalism seems to me grounded in a naturalist substantialism (since it aims at dissolving the abovementioned difference in a common genus, animality), whereas Derrida’s approach ends in a phenomenological primitivism (since it aims at grasping the gaze of the animal through an epoché of the human cultural world). The result is, on the one hand, an essentialist reduction to the One, and, on the other, the nominalist multiplication of the Many. As an alternative to both these perspectives, I share a certain "transcendentalist" approach, in which human difference appears as a capacity to form a world in the Heideggerian meaning, which increases natural reality. The symbol of this new capacity is the upright position, a certain elevation above nature, the sign of which is consciousness. I call this new capacity "diagonal," since, like the diagonal of the square, it is irreducible to its side - to nature (the plane of immanence) -, as much as the human world of "augmented reality" is indeed irreducible to every flat ontology, that is, to an onticology.